PENGARUH INFLASI TERHADAP TINGKAT PENGANGGURAN DI INDONESIA - Dian Yunita Rahayu; Dhita Widya Ramadani; Nadia Ayuninggita Zaldi; Nur Halimah; Rina Yustiani Agustin; Tita Rustika (Jurnal Pijar, 2023)
This study examines the effect of inflation and economic growth on the unemployment rate in Indonesia. Where the purpose of this research is 1). To determine the effect of inflation on the unemployment rate in Indonesia; 2). To determine the effect of economic growth on the unemployment rate in Indonesia; 3). The relationship between inflation and unemployment. The method in this article is a qualitative method with literature studies or library research. The purpose of this article is to analyze existing theories by looking at their comparisons with previous theories in the research literature. The results of this study indicate that inflation is very influential on the unemployment rate in Indonesia, as well as economic growth is very influential and significant on the unemployment rate in Indonesia.